2011
DOI: 10.1007/s00784-011-0559-2
|View full text |Cite
|
Sign up to set email alerts
|

Cytogenetic damage induced by mouthrinses formulations in vivo and in vitro

Abstract: The aim of the present study was to comparatively evaluate DNA damage and cellular death in cells exposed to various commercially available mouthrinses: Listerine Cepacol, Plax alcohol free, Periogard, and Plax Whitening. A total of 75 volunteers were included in the search distributed into five groups containing 15 people each for in vivo study. Exfoliated buccal mucosa cells were collected immediately before mouthrinse exposure and after 2 weeks. Furthermore, blood samples were obtained from three healthy do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
35
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(40 citation statements)
references
References 38 publications
4
35
1
Order By: Relevance
“…MN assays on oral mucosa cells have shown that these biomarkers tend to increase when individuals are exposed temporarily to different substances, such as dental composite materials 21 and mouthwash. 26 The conditions caused by this temporary exposure corroborate our findings, insofar as the greatest increase in the number of MN cells occurred up to 15 days after exposure to CP, regardless of the concentration. Thus, our results suggest that the reduction in the MN production rate from day 15 to 45 indicates that the primary lesions in DNA induced by CP were repaired.…”
Section: Discussionsupporting
confidence: 86%
“…MN assays on oral mucosa cells have shown that these biomarkers tend to increase when individuals are exposed temporarily to different substances, such as dental composite materials 21 and mouthwash. 26 The conditions caused by this temporary exposure corroborate our findings, insofar as the greatest increase in the number of MN cells occurred up to 15 days after exposure to CP, regardless of the concentration. Thus, our results suggest that the reduction in the MN production rate from day 15 to 45 indicates that the primary lesions in DNA induced by CP were repaired.…”
Section: Discussionsupporting
confidence: 86%
“…Another important question is that the occurrence of MNC is small and its distribution is not homogeneous in the sample. These facts explain the large standard deviation commonly found in similar researches and highlights the need for counting a large number of cells in this kind of research to minimize errors (10,12,13,18,24). …”
Section: Discussionmentioning
confidence: 54%
“…MN evaluations are made in buccal epithelial exfoliated cells (BEC) as well, and this test is considered to be the least invasive method available to measure DNA damage in humans (9). Due to its ability to assess the activity of many chemical or physical carcinogenic and mutagenic agents in situ, the MN test in the BEC is the choice of many recent human biomonitoring studies: alcohol (10), tobacco (11), mouthrinses (12) and radiographs (13). …”
Section: Introductionmentioning
confidence: 99%
“…Alcohol-based mouthwashes remain in longer contact with the oral cavity than alcoholic beverages when an alcoholic beverage is ingested. It has been suggested that the use of alcohol-based mouthwashes may exhibit genotoxic effects [5], increase the risk for oral cancer [4], decrease host defence and is one of the stressors [6]. Additionally, the adverse effect of ethyl alcohol on oral tissue and structures have been observed.…”
Section: Introductionmentioning
confidence: 99%